Contribution of calculus 1 and calculus 2 skills to learning outcomes in machine and artificial intelligence courses - Farida, Anisatul (LINEAR: Journal of Mathematics Education, 2025)
This study investigates the influence of students' abilities in Calculus I and Calculus II on their academic performance in the Machine and Artificial Intelligence course. The research explores explicitly three aspects: (1) the individual contribution of Calculus I, (2) the individual contribution of Calculus II, and (3) the combined effect of both on learning outcomes. Using an associative quantitative method, the study involved 35 first-semester Informatics Engineering students at Duta Bangsa University, selected through quota sampling. Data were gathered through tests and documentation and analyzed using multiple linear regression in SPSS with a 5% significance level. The results reveal that Calculus I ability does not have a statistically significant effect on student performance. In contrast, Calculus II's ability demonstrates a significant positive impact. Furthermore, the combined abilities in Calculus I and II significantly influence learning outcomes in the course. These findings highlight the essential role of Calculus II in enhancing students' comprehension of complex topics in artificial intelligence and machine learning, suggesting that a stronger foundation in advanced calculus may better prepare students for success in related fields.